2017
DOI: 10.5380/rsa.v18i2.50371
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho Do Modelo Swat Para Diferentes Critérios De Geração De Unidades De Resposta Hidrológica

Abstract: Resumo -A subjetividade no uso do modelo SWAT, no que diz respeito à discretização espacial da bacia em subbacias juntamente com a geração das unidades de resposta hidrológica (HRUs) foi a questão que motivou a elaboração deste artigo. Foram comparadas as vazões mensais obtidas com o modelo SWAT na simulação de uma bacia hidrográfica com 2030 Km 2 de área de drenagem (rio Grande, MG), adotando diferentes critérios de geração de HRUs, bem como de discretização espacial em sub-bacias. Baseado nos resultados, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…Pbias (Percent bias) values also showed good adherence between the estimated and observed data by the model. The ideal value for Pbias is 0 (zero), with negative values indicating that the model underestimates the flow and positive values overestimate the same (Bueno et al, 2017). In the present case, there was a small overestimation of the flow values in the calibration period (0.2%) and a short underestimation in the validation period (-0.8%).…”
Section: Resultsmentioning
confidence: 42%
See 1 more Smart Citation
“…Pbias (Percent bias) values also showed good adherence between the estimated and observed data by the model. The ideal value for Pbias is 0 (zero), with negative values indicating that the model underestimates the flow and positive values overestimate the same (Bueno et al, 2017). In the present case, there was a small overestimation of the flow values in the calibration period (0.2%) and a short underestimation in the validation period (-0.8%).…”
Section: Resultsmentioning
confidence: 42%
“…The choice of parameters used for model calibration was based on literature review and parameter sensitivity analysis (Santhi, 2001;Yang, 2008;Bueno et al, 2017). The literature review indicated the most commonly used parameters and the sensitivity analysis provided more detailed information about the importance and representativeness of each of these parameters for BHM.…”
Section: Figure 1 Location Of Flow Rates In Bhmmentioning
confidence: 99%
“…Para a modelagem hidrológica, o SWAT considera três níveis de escala espacial: bacia hidrográfica, sub-bacias e Unidades de Resposta Hidrológica (HRUs) (Melo Neto et al, 2014). As unidades de resposta hidrológica (HRUs), definidas como combinações únicas de vegetação, solos e relevo, são geradas individualmente em cada sub-bacia (Bueno et. al, 2017).…”
Section: Unidade De Resposta Hidrológica (Hru)unclassified
“…Nesse caso estabelece-se, para cada mapa, um percentual mínimo de ocupação da área da sub-bacia para que seja definida uma HRU. Para esta opção, ao invés de um percentual da área total, pode ser adotado um valor mínimo de área (em ha), o qual será observado para criação das HRUs (Bueno et al, 2017). Neste trabalho, para a geração de HRUs múltiplas foi utilizado um thereshold (limite mínimo de área) de 10% de uso do solo, tipo de solo e declividade.…”
Section: Unidade De Resposta Hidrológica (Hru)unclassified